Non-destructive testing and condition monitoring techniques for renewable energy industrial assets - Papaelias, Mayorkinos; Garcia, Fausto Pedro; Karyotakis, Alexander (Butterworth-Heinemann, an imprint of Elsevier, 2020)
Non-Destructive Testing and Condition Monitoring Techniques for Renewable Energy Industrial Assets integrates state-of-the-art information and discusses future developments and their significance to the improvement of the renewable energy industry. Renewable energy assets are complex systems with several critical components that require inspection and adequate maintenance in order to ensure their high availability and uninterrupted operation. This is the first book to apply NDT and condition monitoring to these complex systems. -- Provided by publisher.
Keywords: Energy industries.; Renewable energy sources.; Nondestructive testing.; elektronické knihy; electronic books